ANALISIS PENERAPAN SISTEM EVALUASI AKADEMIK TERPADU (SIETA) DI SMKN 1 BLEGA - Ramadani, Hazra Farahiyah; Hartati, Sulis Janu; Hanifah, Sri Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
One of the important competence that teacher should have is the ability to evaluate. In this digital era, teachers are required to be able to utilize various technology that can that can make the assessment process more effective. Sistem Evaluasi Terpadu (SIETA) became one of the platform that chosen by SMKN 1 Blega. This study uses quantitative descriptive methods to describe the teacher’s digital competency and role as an evaluator. This study uses instrument such as (1) questionnaire, (2) observation sheets; (3) documentation to collect the data needed. This study was conducted on 30 teachers by using sample paired t test on pretest and posttest of the research subject. The result of the study shows that there is an increase of teacher’s digital competence and their role as an evaluator after the implementation of SIETA.